Pamietniki z getta warszawskiego : fragmenty i regesty - Grynberg, Michal (Warszawa : Wydawn. Nauk. PWN, 1993)
This is a collection of reminiscences of people who passed through the Warsaw Ghetto during World War II.
Table of contents in English and in German.
Notes bibliogr. Index.
Keywords: Holocaust, Jewish (1939-1945) -- Poland -- Warsaw -- Sources; Holocaust, Jewish (1939-1945) -- Personal narratives; World War, 1939-1945 -- Personal narratives, Jewish; Jews -- Poland -- Warsaw -- Biography; World War, 1939-1945 -- Jews -- Poland -- Warsaw; Warsaw (Poland) -- History -- Warsaw Ghetto Uprising, 1943 -- Sources